Signos y síntomas de desórdenes temporomandibulares antes y después de cirugía ortognática, comparación entre osteotomía sagital y osteotomía oblicua de rama - Sandra P. Jaramillo-M; Andrés F. Del Valle-R (Universidad de Antioquia, 2005)
The purpose of this study was to investigate the influence of orthognatic surgery on sings and symptoms of tempormandibular joint dysfunction (TMD). 16 patients with esqueletic class iii pattern were examined before and after orthognathic surgery. Eight of the patients underwent intraoral oblique osteotomy (IORO) and the other eight received sagital split ramus osteotomy (SSRO). In addition, two patients of each group received a Le Fort i osteotomy. Patients were evaluated for signs and symptoms related to TMD before surgery and changes in those were recorded at one, three and six mouths after intervention. There were not significant differences in the frequencies of temporomandibular joint (TMJ) sounds, TMJ pain or muscular pain between cases of both groups. Improvement in signs and symptoms of TMD was noticed in all patients, although, a postoperative reduction in mandibular aperture was also evident. A significant improvement in the frequency of headache was reported for five out of six patients after the surgery. The results of this study show that IORO and SSRO can improved TMD signs and symptoms, but no significant differences were observed between these procedures. The numberof cases included are reduced and limit the power of the results.